Association between germline pathogenic variants and breast cancer risk in Japanese women: The HERPACC study. Issue 4 (7th March 2022) - Kasugai, Yumiko; Kohmoto, Tomohiro; Taniyama, Yukari; Koyanagi, Yuriko N.; Usui, Yoshiaki; Iwase, Madoka; Oze, Isao; Yamaguchi, Rui; Ito, Hidemi; Imoto, Issei; Matsuo, Keitaro
Abstract: Approximately 5%–10% of breast cancers are hereditary, caused by germline pathogenic variants (GPVs) in breast cancer predisposition genes. To date, most studies of the prevalence of GPVs and risk of breast cancer for each gene based on cases and noncancer controls have been conducted in Europe and the United States, and little information from Japanese populations is available. Furthermore, no studies considered confounding by established environmental factors and single‐nucleotide polymorphisms (SNPs) identified in genome‐wide association studies (GWAS) together in GPV evaluation. To evaluate the association between GPVs in nine established breast cancer predisposition genes including BRCA1 / 2 and breast cancer risk in Japanese women comprehensively, we conducted a case‐control study within the Hospital‐based Epidemiologic Research Program at Aichi Cancer Center (629 cases and 1153 controls). The associations between GPVs and the risk of breast cancer were assessed by odds ratios (OR) and 95% confidence intervals (CI) using logistic regression models adjusted for potential confounders. A total of 25 GPVs were detected among all cases (4.0%: 95% CI: 2.6–5.9), whereas four individuals carried GPVs in all controls (0.4%). The OR for breast cancer by all GPVs and by GPVs in BRCA1 / 2 was 12.2 (4.4–34.0, p  = 1.74E‐06) and 16.0 (4.2–60.9, p  = 5.03E‐0.5), respectively. A potential confounding with GPVs was observed for the GWAS‐identified SNPs, whereas not for established environmental risk factors. In conclusion, GPVs increase the risk of breast cancer in Japanese women regardless of environmental factors and GWAS‐identified SNPs. Future studies investigating interactions with environment and SNPs are warranted. Abstract : To evaluate the association between germline pathogenic variants (GPVs) in nine established breast cancer predisposition genes including BRCA1/2 and breast cancer risk in Japanese women comprehensively, we conducted a case‐control study (629 cases and 1153 controls) adjusted for potential confounders. A potential confounding with GPVs was observed for the genome‐wide association studies (GWAS)‐identified SNPs, whereas not for established environmental risk factors. GPVs increase the risk of breast cancer in Japanese women regardless of environmental factors and GWAS‐identified SNPs.